Brake dust exposure exacerbates inflammation and transiently compromises phagocytosis in macrophages - Selley, Liza; Schuster, Linda; Marbach, Helene; Forsthuber, Theresa; Forbes, Ben; Gant, Timothy W.; Sandström, Thomas; Camiña, Nuria; Athersuch, Toby J.; Mudway, Ian; Kumar, Abhinav (Metallomics, 2020)
Studies have emphasised the importance of combustion-derived particles in eliciting adverse health effects, especially those produced by diesel vehicles. In contrast, few investigations have explored the potential toxicity of particles derived from tyre and brake wear, despite their significant contributions to total roadside particulate mass. The objective of this study was to compare the relative toxicity of compositionally distinct brake abrasion dust (BAD) and diesel exhaust particles (DEP) in a cellular model that is relevant to human airways. Although BAD contained considerably more metals/metalloids than DEP (as determined by inductively coupled plasma mass spectrometry) similar toxicological profiles were observed in U937 monocyte-derived macrophages following 24 h exposures to 4-25 μg ml−1 doses of either particle type. Responses to the particles were characterised by dose-dependent decreases in mitochondrial depolarisation (p ≤ 0.001), increased secretion of IL-8, IL-10 and TNF-α (p ≤ 0.05 to p ≤ 0.001) and decreased phagocytosis of S. aureus (p ≤ 0.001). This phagocytic deficit recovered, and the inflammatory response resolved when challenged cells were incubated for a further 24 h in particle-free media. These responses were abrogated by metal chelation using desferroxamine. At minimally cytotoxic doses both DEP and BAD perturbed bacterial clearance and promoted inflammatory responses in U937 cells with similar potency. These data emphasise the requirement to consider contributions of abrasion particles to traffic-related clinical health effects.
Gesehen am 15.05.2020